ANALISIS NILAI TAMBAH KOPRA ASAP DAN KOPRA JEMUR (STUDI KASUS DI DESA BUYAT KECAMATAN KOTABUNAN KABUPATEN BO-LAANG MONGONDOW TIMUR) (Value Added Analysis of Copra and Sun Dried Copra in Buyat Village Kotabunan Sub District East Bolaang Mongondow Regency - Rena Triana Hermanto; Eyverson Ruauw; Rine Kaunang (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2020)
The research result showed that the cost structure of copra and sun dried copra , which is variable costs where raw materials, supporting materials, transportation and labor costs are components of variable cost formation and and fixed costs that have components of formation including land tax costs and depreciation Total cost that includes fixed and variable costs. The revenue of sun dried copra on average, each month, uses ± 4,980 kg of copra with revenue , which is Rp. 18,924,000 and the sun dried copra, every month uses ± 5,240 kg of copra with a revenue of Rp. 24,104,000. Processing of copra and sun dried copra as a whole can benefit and deserve to be developed. This is based on the results of the added value obtained by sun dried copra , that is, the gross added value of Rp. 8,939,000, net value added Rp.8,808,574, value added per raw material Rp. 897.45 / kg and sun dried copra which is gross added value Rp. 13,109,200, net added value of Rp. 13,013,388, value added per raw material Rp. 1,250.8 / kg. Keywords: Value Added and Revenue